The subcutaneous implantable cardioverter defibrillator in daily clinical practice - Tardu Özkartal; Alexander Breitenstein; Ardan M. Saguner; Devdas T. Inderbitzin; Markus J. Wilhelm; Stefano Benussi; Francesco Maisano; Thomas F. Lüscher; Frank Ruschitzka; Jan Steffel (Swiss Medical Weekly, 2017)
INTRODUCTION